Creating authenticity. Authentication processes in ethnographic museums - Geurds, Alexander; Van Broekhoven, Laura (Mededelingen van het Rijksmuseum voor Volkenkunde ;, 2013)
'Authenticity' and authentication is at the heart of museums' concerns in displays, objects, and interaction with visitors. These notions have formed a central element in early thought on culture and collecting. Nineteenth century-explorers, commissioned museum collectors and pioneering ethnographers attempted to lay bare the essences of cultures through collecting and studying objects from distant communities. Comparably, historical archaeology departed from the idea that cultures were discrete bounded entities, subject to divergence but precisely therefore also to be traced back and linked t.